Self-realization of the employees of the mayor of Rioverde, San Luis Potosi, Mexico - Gómez-Sánchez, David (Universidad Autónoma de Tamaulipas, 2012)
In the present study point to selfrealization of any clerk of Presidencia Municipal de Rioverde, S.L.P., which is the main objective of the study. This was carried out in order to identify the relationship between the factors involved in the self (the Core of the self-realization, Jonah complex, Curiosity, Well-being in solitude, Openness to experience, Purpose and meaning to life and Democratic character). Test was used Kolmogorov-Smirnov normality and bivariate analysis statistics techniques rho Spearman, the test of analysis of variance (Anova) and t test for independent samples. It was found that the score of the dimensions of self-realization is high in most of these; there is also evidence of the relationship between all dimensions of self-realization and some demographic characteristics of the person.